Catechol‐O‐methyltransferase gene val158met polymorphism and depressive symptoms during early childhood12. Issue 3 (8th March 2013) - Sheikh, Haroon I.; Kryski, Katie R.; Smith, Heather J.; Dougherty, Lea R.; Klein, Daniel N.; Bufferd, Sara J.; Singh, Shiva M.; Hayden, Elizabeth P.
Abstract Catechol‐O‐Methyltransferase (COMT) is a critical regulator of catecholamine levels in the brain. A functional polymorphism of the COMT gene, val158met, has been linked to internalizing symptoms (i.e., depression and anxiety) in adolescents and adults. We extended this research by investigating whether the val158met polymorphism was associated with childhood symptoms of depression and anxiety in two independent samples of young children (Ns = 476 and 409). In both samples, preschool‐aged children were genotyped for the COMT val158met polymorphism. Symptoms of psychopathology were assessed via parent interviews and primary caregiver reports. In both samples, children homozygous for the val allele had higher levels of depressive symptoms compared to children with at least one copy of the met allele. Our findings extend previous research in older participants by showing links between the COMT val158met polymorphism and internalizing symptoms in early childhood. © 2013 Wiley Periodicals, Inc.